Optimizing Cash Waqf for Productive Ventures: A Comparative Juridical Study of Indonesia and Malaysia - Istianah Zainal Asyiqin (Greenation Research & Yayasan Global Resarch National, 2023)
This research examines the regulation and governance of cash waqf for productive ventures in Indonesia and Malaysia. It focuses on how both countries develop legal and institutional frameworks to optimize cash waqf as an instrument for economic empowerment and social welfare. This study uses a normative juridical method with statutory, conceptual, and comparative approaches. The data were obtained through library research by analyzing laws, regulations, journal articles, books, and other relevant legal materials related to cash waqf and waqf governance. The findings show that Indonesia regulates waqf through a national legal framework under Law Number 41 of 2004 on Waqf, with the Indonesian Waqf Board playing an important supervisory role. Malaysia applies a decentralized model, where State Islamic Religious Councils act as sole trustees for waqf assets in their respective states. Although both countries recognize the potential of cash waqf for productive ventures, they still face challenges related to public literacy, institutional capacity, transparency, and effective fund management. This study argues that stronger regulation, accountable governance, and wider public participation are needed to optimize cash waqf for sustainable economic development and community welfare.